Pola Interaksi Guru Dengan Peserta Didik Perspektif Alquran Surah Luqman Ayat 12 - 19 - Sunardi; Khairul Fatihin (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: Digging and studying more intensely what is contained in the Koran, then we will find various kinds of messages related to education, one of which is an interesting story about the process of educational interaction and learning between father and son. In this story, if we look at the philosophical meaning, we will find several concept s, patterns or models of education. In the Koran, Luqman verses 12 - 19 . Describe the story of how God rewards the figure of the father by perpetuating his name as the name of the Qur'anic story because of his diligent efforts to provide education and learni ng to his children with noble lessons. The focus that will be examined in this study is the pattern of teacher interaction with students from the perspective of the Qur'an Surah Luqman verses 12 - 19 . This research is a research library research, which is co llecting theoretical data as a scientific presentation carried out by selecting literature related to research. Technical analysis of data uses content analysis, analyzes critically the relevant data. This research concludes that the Pattern of Teacher Int eraction with Students Perspective of Surah Luqman Alquran Verses 12 - 19 , the author can draw conclusions that: a. the teacher's role in learning is the teacher as an educator, the teacher as a guide, and the teacher as an advisor. b. the values of educat ion are the education of faith (faith), religious education, and moral education, c. teacher interaction patterns with students used are one - way relationship patterns.